Promoting inclusivity and equity in information and communications technology for food, land, and water systems - Ng, Michelle; Haan, Nicoline C. de; King, Brian; Langan, Simon J. (CGIAR Platform for Big Data in Agriculture, 2021)
Food, land, and water systems underpin the health of societies and the environment, yet they are facing pressure from climate change, population growth, urbanization, and the overexploitation of natural resources. Information and Communication Technologies (ICTs) have the potential to support food, land, and water systems in response to these challenges. This report explores issues of inclusivity and equity of ICTs and how these technologies might be better used to their full potential.